Improving the Achievement of Learning Indonesian Through the Problem Based Learning Method in SDN 2 Getas - Sumaryati Sumaryati (Universitas Sebelas Maret, 2020)
The purpose of this study was to increase the interest and learning outcomes of students in the Indonesian language muple in grade III elementary schools with the Problem Based Learning (PBM) learning model. The research conducted was a Classroom Action Research (CAR) in two cycles, with each cycle consisting of one meeting. The stages of each cycle are planning, implementing, observing and reflecting. Each meeting was carried out a pretest and post test to determine the development of students in cycle I 75% of students who complete after carrying out post tests. In cycle II participants Students who complete after carrying out the post test are 100%. These results indicate that the Problem Based Learning (PBM) learning model can improve student learning outcomes, especially the Indonesian language muple SDN 2 Getas.